Persian fencing techniques - Khorasani, Manouchehr Moshtagh (Revista de Artes Marciales Asiáticas, 2012)
There are numerous manuscripts, poems and stories that describe, specifically and in detail, the different techniques used in Persian swordsmanship. The present article explains the origins and the techniques of Persian swordsmanship. The article also describes the traditional code of conduct for Persian warriors. Additionally, it describes an array of techniques that were deployed in actual combat in Iran’s history. Some of these techniques are represented via the miniatures that are reproduced herein. This is the first article on Persian swordsmanship published in any periodical.